17. Nuevos nombres para dos subasociaciones de Poo bulbosae-Trifolietum subterranei Rivas Goday 1964 - Ladero, Miguel; Amigo, Javier; Romero, María lnmaculada (Lazaroa, 2014)
Nuevos nombres para dos subasociaciones de Poo bulbosae-Trifolietum subterranei Rivas Goday 1964.